Peningkatan Loyalitas Mahasiswa Yang Dipengaruhi Oleh Kualitas Pelayanan Akademik dan Kepuasan Mahasiswa (Studi Kasus Pada Mahasiswa S1 Dan D3 STIESIA Surabaya) - Novianto Eko Nugroho (Jurnal Sosial Humaniora, 2020)
Higher Education is the highest level of education in the education servicebusiness in Indonesia which produces bachelor or diploma graduates to meetthe competitive needs of the workforce. This study aims to analyze theincrease in student loyalty which is influenced by the quality of academicservices and satisfaction of S1 and D3 STIESIA Surabaya students. This studyuses a quantitative approach to determine the correlation of student loyaltywhich is influenced by the role of academic service quality and studentsatisfaction. This research method uses path analysis. The results showed anincrease in student loyalty which was influenced by the role of academicservice quality due to high student satisfaction.